Broadside and map - Spence-Hermitt, I. (1849)
Broadside of Moreton Bay Courier extraordinary of Brisbane, Monday evening, July 2 1849. On the back is an MS map of the Moreton Bay area and rivers running into it purporting to be by I. Spence-Hermitt.
Manuscript reference no. : NLA MS 2984.
Keywords: Moreton Bay Region (Qld.) -- Maps